The proper timing of virtual reality experience for reducing preoperative anxiety of pediatric patients: A randomized clinical trial - Ryu, Jung-Hee; Ko, Dayoung; Han, Ji-Won; Park, Jin-Woo; Shin, Aesun; Han, Sung-Hee; Kim, Hyun-Young (Frontiers in Pediatrics, 2022)
Background The virtual reality (VR) experience of operation room (OR) prior to anesthesia and surgery has been known to reduce the anxiety and distress of pediatric patients. However, the proper timing of this VR experience is unknown. The purpose of this randomized clinical study was to evaluate the proper timing of a VR tour of OR (a few days before vs. immediately before anesthesia) to reduce the anxiety in a pediatric patient undergoing elective surgery. Methods A total of 105 children aged 4-10 years were randomly divided into 3 groups. Control group received standard verbal information about the process of anesthesia and surgery 10 min before anesthesia. VR A group experienced VR tour at the outpatient clinic a few days before anesthesia, whereas VR B group experienced VR tour 10 min before anesthesia at the reception area of OR. The 4-min VR video used in this study showed the experience of Pororo, an animation character, entering OR from the entrance and undergoing anesthesia. We evaluated the anxiety of children using modified Yale preoperative anxiety scale (m-YPAS), the anxiety of caregiver using Beck anxiety inventory (BAI), and caregiver’s satisfaction. Results The m-YPAS of VR B group was significantly lower than that of control and VR A group (p = 0.001) whereas there was no statistical significant difference in BAI (p = 0.605) among the 3 groups. The score of caregiver’s satisfaction about the overall process of anesthesia and surgery was higher in VR A group than in control and VR B groups (p = 0.054). Conclusions The VR experience of OR immediately before anesthesia was more effective than standard verbal information or VR tour at the outpatient clinic a few days before anesthesia in reducing the anxiety and distress of children prior to surgery.